2006
DOI: 10.1016/j.virol.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity of the VP2 gene of a canine parvovirus strain detected in a domestic cat

Abstract: This study reports the detection of co-infection by multiple CPV variants and the high genetic complexity of a CPV-2 strain detected in a domestic cat. The CPV variants selected by cloning the VP2 gene were sequenced, and genetic diversity and selection pressure were investigated. Comparison of the nucleotide sequences has evidenced 10 different viral populations, and, in the same animal, more CPV variants coexist. Our analysis excludes the possibility that the recombination events took place during infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 18 publications
3
44
0
1
Order By: Relevance
“…The high differentiation in the case of parvoviruses is also confirmed by research on CPV-2, in the case of which numerous genetic variants may attack a single individual [19]. In the presented study, marked differences were observed between the wild and farmed groups.…”
Section: Discussionsupporting
confidence: 75%
“…The high differentiation in the case of parvoviruses is also confirmed by research on CPV-2, in the case of which numerous genetic variants may attack a single individual [19]. In the presented study, marked differences were observed between the wild and farmed groups.…”
Section: Discussionsupporting
confidence: 75%
“…Residue 297 is located in the antigenic region close to epitope B and substitutions at this position may be responsible for changes in antigenicity of CPV-2 variants (Truyen, 2006). Analogously, a change at position 440 (TAA) has been described for Italian, Indian, Korean and American CPV-2 isolates (Battilani et al, 2002;Chinchkar et al, 2006;Kang et al, 2008;Kapil et al, 2007) and for a clone from a mixed CPV-2 population detected in a domestic cat from Italy (Battilani et al, 2006b). As for the FPLV strains, that change is a consequence of a first-base mutation (A1318G).…”
Section: Discussionmentioning
confidence: 87%
“…CPV-2a and -2b viruses have been also isolated in feline cells in vitro and in domestic cats in vivo from Japan, USA, Taiwan and Vietnam (Truyen et al, 1995(Truyen et al, , 1996aMochizuki et al, 1996;Ikeda et al, 2000). Diseased cats have also been detected with CPV-2c (Miranda et al, 2014) or co-infections by multiple CPV variants (Battilani et al, 2006) or mixed infections with FPV and CVP-2-like (Url et al, 2003;Battilani et al, 2011). Some studies have also reported the presence of CPV-2 variants in faecal and bone marrow samples of healthy cats (Clegg et al, 2012;Haynes & Holloway, 2012).…”
Section: Host Ranges For Antigenic Cpv-2 Variants Domestic Catsmentioning
confidence: 99%